Original researchRisk factor control and adherence to treatment in patients with coronary heart disease in the Republic of Srpska, Bosnia and Herzegovina in 2005-2006 - Vulic, Dusko; Loncar, Sasa; Krneta, Milenko; Skrbic, Ranko; Lazarevic, Aleksandar; Lee, Brian T.; Lopez, Victor A.; Wong, Nathan D. (Archives of Medical Science, 2010)
Introduction: European treatment guidelines in persons with known coronary heart disease (CHD) focus on adherence to antiplatelet therapy, β-blockers, ACE/ARBs, and lipid-lowering agents, with goals for blood pressure (BP) of < 140/90 mm Hg and LDL cholesterol of < 3.0 mmol/l. Data on adherence to these measures in Eastern Europe are limited. Material and methods: The Third Republic of Srpska, Bosnia and Herzegovina, Coronary Prevention Study (ROSCOPS III) was conducted in 2005-2006 at 10 primary heath care centres in 601 patients (36% female, mean age 55 years) with CHD including acute myocardial infarction or ischaemia, coronary artery bypass graft, or angioplasty who were examined and interviewed at least 6 months after the event. We examined the proportion of subjects on recommended treatments and at goal for BP, LDL-C, and non-smoking. Results: The proportion of subjects on recommended treatments included 61% for β-blockers, 79% for ACE/ARBs, 63% for lipid-lowering agents and 74% for antiplatelet therapy. Only 30% of subjects were on all four of these treatments. 59% of subjects had BP at goal of < 140/90 mm Hg and 33% were controlled to < 130/80 mm Hg, 41% for LDL-C, and 88% were non-smokers. Improvements were seen in lipid-lowering and ACE/ARB drug use and non-smoking status from an earlier survey (ROSCOPS II) in 2002-2003. Conclusions: Our data show, despite improvement over recent years, that many persons with CHD in the Republic of Srpska, Bosnia and Herzegovina are neither on recommended treatments nor at target for BP and/or LDL-C. Improved efforts targeted at both physicians and patients to address these issues are needed.